2019
DOI: 10.1002/jbmr.3895
|View full text |Cite
|
Sign up to set email alerts
|

Greater Bone Marrow Adiposity Predicts Bone Loss in Older Women

Abstract: Bone marrow adiposity (BMA) is associated with aging and osteoporosis, but whether BMA can predict bone loss and fractures remains unknown. Using data from the Age Gene/Environment Susceptibility (AGES)-Reykjavik study, we investigated the associations between 1 H-MRS-based measures of vertebral bone marrow adipose tissue (BMAT), annualized change in bone density/ strength by quantitative computed tomography (QCT) and DXA, and secondarily, with incident clinical fractures and radiographic vertebral fractures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 30 publications
1
39
0
2
Order By: Relevance
“…Sollmann et al reported significant correlations between PDFF of the lumbar bone marrow and the local musculature in postmenopausal, but not in premenopausal women 12 . This seemingly contradictory finding may be explained by the different anatomical locations www.nature.com/scientificreports www.nature.com/scientificreports/ investigated and the fact that our analysis comprised a relatively young study population as compared to the postmenopausal women included by Sollmann et al An inverse correlation between age and bone mineral density (BMD) was shown by several groups in the past 34,35 . In older adults, higher vertebral bone marrow fat has been shown to be associated with lower trabecular BMD and vertebral fractures 36 .…”
Section: Discussionmentioning
confidence: 88%
“…Sollmann et al reported significant correlations between PDFF of the lumbar bone marrow and the local musculature in postmenopausal, but not in premenopausal women 12 . This seemingly contradictory finding may be explained by the different anatomical locations www.nature.com/scientificreports www.nature.com/scientificreports/ investigated and the fact that our analysis comprised a relatively young study population as compared to the postmenopausal women included by Sollmann et al An inverse correlation between age and bone mineral density (BMD) was shown by several groups in the past 34,35 . In older adults, higher vertebral bone marrow fat has been shown to be associated with lower trabecular BMD and vertebral fractures 36 .…”
Section: Discussionmentioning
confidence: 88%
“…MPC2 cells consistently produced high levels of the transcriptional regulator of adipogenesis, PPARγ as well as other proteins characteristic of adipocytes including adiponectin, perilipin, and fatty acid binding protein 4. Recent studies have shown that accumulation of adipose tissue within the bone marrow is detrimental to skeletal health and is associated with aging and disuse 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported no association between bone marrow adipose tissue and bone density/ strength nor with incident fractures. However, they reported that greater bone marrow fat was associated prospectively with greater loss of trabecular bone at the spine and femoral neck, and greater loss of spine compressive strength, in older women [46]. The study by Sheu et al found significant inverse correlations between bone marrow fat estimated with MRI and BMD (− 0.30 for femoral neck and − 0.39 for total hip) among men with diabetes but not among those without diabetes [47].…”
Section: Pathophysiology Of Non-vertebral and Vertebral Fracture Riskmentioning
confidence: 97%